Matemática
marcellazevedo
16

Alguém pode me ajudar? Equação 3x² + 5x = -x -9 + 2x²

+1
(1) Respostas
Wallter

3x² + 5x = - x - 9 + 2x² 3x² - 2x² + 5x + x + 9 = 0 x² + 6x + 9 = 0 a = 1               b = 6                  c = 9 ∆ = b²- 4 . a . c  ∆ = 6² - 4 * 1 * 9 ∆ = 36 - 36 ∆ = 0 Nota: Quando o ∆ (Delta) for igual a 0 (zero) teremos apenas 1 (uma) raiz. x = - b ± √∆        ------------           2a x = - 6 ± √0        ------------           2 * 1 x =  - 6 + 0       ------------            2 x = - 6 + 0           2 x = - 6 : 2 x = - 3 Resposta: x = {- 3}

Adicionar resposta